2020
DOI: 10.3390/ijms21124461
|View full text |Cite
|
Sign up to set email alerts
|

Phloem Exudate Protein Profiles during Drought and Recovery Reveal Abiotic Stress Responses in Tomato Vasculature

Abstract: Drought is the leading cause of agricultural yield loss among all abiotic stresses, and the link between water deficit and phloem protein contents is relatively unexplored. Here we collected phloem exudates from Solanum lycopersicum leaves during periods of drought stress and recovery. Our analysis identified 2558 proteins, the most abundant of which were previously localized to the phloem. Independent of drought, enrichment analysis of the total phloem exudate protein profiles from all samples suggests that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 91 publications
0
13
0
Order By: Relevance
“…Ogden et al . [ 46 ] observed 169 proteins that exhibit significant changes in abundance within tomato phloem sap during periods of drought and recovery. Jakobs and Müller [ 47 ] found that aphid infestation of Tanacetum vulgare leads to changes in phloem sap chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Ogden et al . [ 46 ] observed 169 proteins that exhibit significant changes in abundance within tomato phloem sap during periods of drought and recovery. Jakobs and Müller [ 47 ] found that aphid infestation of Tanacetum vulgare leads to changes in phloem sap chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Luckily, the recent advances in technologies allowing large-scale “–omics” analyses accelerate this process. The studies in this Special Issue add valuable pieces of the puzzle related to stress responses by: (i) reporting novel potent regulators and the mechanisms through which they exert their effects [ 15 , 17 , 18 , 19 ]; (ii) throwing light on previously unexplored components [ 16 ] or the pathways involved in particular stress types [ 11 , 12 , 13 ]; or (iii) exploring strategies to mitigate the detrimental effects [ 14 ]. We are confident that they will inspire further productive research in the future.…”
Section: Discussionmentioning
confidence: 99%
“…One such example is phloem sap, whose dynamics in response to abiotic stress is relatively unexplored. Ogden et al [ 16 ] provided one comprehensive snapshot of the protein composition of phloem sap during drought and subsequent recovery in tomato. Using a proteomic approach (LC-MS/MS), the authors detected 2558 novel or previously described proteins, involved in various biological processes.…”
Section: Genetic and Systems Biology Approaches Revealing The Compmentioning
confidence: 99%
See 1 more Smart Citation
“…In this proteomics study, Castañeda et al described the existence of a core stress responsive proteome in M. truncatula across different tissues including the phloem sap, suggesting a major role of the phloem in stress protection and antioxidant activity, especially by linking below and above ground communication in order to fine-tune stress response [ 15 ]. Other studies considering the phloem sap and different water-deficit stresses have been made in tomato [ 16 , 17 ], Plantago major [ 18 ], white clover [ 19 ], Ricinus communis [ 20 ], maize [ 21 ] and alfalfa [ 22 ].…”
Section: Introductionmentioning
confidence: 99%